Ball milling pretreatment facilitating α-amylase hydrolysis for production of starch-based bio-latex with high performance. (15th August 2020) - Liu, Liqin; An, Xingye; Zhang, Hao; Lu, Zonghong; Nie, Shuangxi; Cao, Haibing; Xu, Qingliang; Liu, Hongbin
Highlights: Cassava based bio-latex with high coating performance was prepared. Ball milling can efficiently destroy the crystalline structure of starch granules. α-Amylase hydrolysis of milled starch granules generated more activated starch chains. H2 O2 oxidation and SHMP cross-linking processes were improved for bio-latex production. Abstract: Starch based bio-latex has been widely researched in the coating paper area for the purpose of partial replacement of petroleum-based binders. In this paper, a green and facile ball milling pretreatment was proposed to modify the starch granules before α-amylase hydrolysis by breaking up their crystalline structure, thus improving the accessibility and susceptibility of amylase into starch structure. It was found that the improved hydrolysis process after 8 h ball milling can generate suitable degree of polymerization of polysaccharides or oligosaccharides, which further facilitated the following H2 O2 oxidation and SHMP crosslinking processes. In addition, a mechanism was also demonstrated to illustrate the improvement induced by ball milling pretreatment. The prepared bio-latex with crosslinking-structure performed excellent adhesive properties when substituted 25 % of petroleum-based latex during paper coating application, which showed great potential in improving the economic, cost, and environment benefits of traditional production of coated paper.